The Practice of Prolonging Meropenem Infusion: A Narrative Review of Literatures Over the Last Decade: The Practice of Prolonging Meropenem Infusion: A Narrative Review of Literatures Over the Last Decade - Fauzi, Rifani; Widyati, Widyati; Sari, Ika Puspita (Jurnal Surya Medika (JSM), 2024)
Background: The emergence of Antimicrobial Resistance (AMR) has forced clinicians and medical professionals to implement a strict Antimicrobial Stewardship policy. One of the pillar of Antimicrobial Stewardship is by optimizing the use of antibiotic agents. Beta-lactams demonstrate a time-dependent effect in combating bacteria. Since it is pharmacodynamically supported, a prolonged exposure via intravenous administration could be a feasible strategy to maximize the bactericidal effect. Meropenem, a beta-lactam antibiotic of carbapenems sub-class, also falls into the category above. However, there are questions to be answered regarding its stability, compatibility, safety, and clinical outcomes superiority compared to the standard intermittent infusion, before we can determine its effectiveness to be delivered as prolonged or extended infusion. Aims: This article would like to review literatures regarding the rationale behind the practice of prolonging meropenem infusion from the last decade. Method: For this narrative review we utilized articles extracted from Cochrane Library, ScienceDirect, and SageJournals databases from the last ten years. We also added complementary related articles from UpToDate®. Selected articles were limited to those published in english. Inclusion criteria specifically only including related articles to the practice of prolonging meropenem infusion on adult patients. A total of 18 articles were reviewed for the synthesis of this narrative review. Conclusion: Meropenem is eligible for prolonged infusion protocol since it is theoretically supported, adequate in stability, less concern for incompatibility, and potentially can provide better clinical outcomes compared to standard intermittent infusion.